Effect of temperature on immunocompetence of the blue mussel (Mytilus edulis) - Alexandre Beaudry; Marlène Fortier; Stéphane Masson; Michel Auffret; Pauline Brousseau; Michel Fournier (MDPI AG, 2016)
The blue mussel is a filter-feeding bivalve commonly used in ecotoxicological monitoring as a sentinel species. Due to climate change and the increase of temperature expected in marine environment, it is important to anticipate potential impacts on this species. The aim of this study was to investigate the immunocompetence of blue mussels acclimated to different temperatures and on the effects of increasing temperatures (5, 10 and 20°C). Different indices and gonad maturation stages were also determined throughout the experiments. Cell viability, phagocytosis, serum lysozyme activity and cyclooxygenase (COX) activity were evaluated as immune parameters. The cellular immunity was also evaluated after hemocytes exposure to various cadmium concentrations in vitro. The results obtained demonstrate modulation of hemocyte viability and the ability of these cells to phagocytize in absence of contaminants. After the exposure to cadmium, hemocytes showed greater viability at 5°C while maintaining a higher phagocytic competence. In addition, the lysozyme activity stayed stable at all tested temperatures, contrary to that of COX, which increased when the mussels were maintained at 20°C. The evaluation of indices demonstrated no reduction of general conditions during all the experiment despite the increase of temperature and the reduction of the digestive gland weight. Moreover, the lack of food does not affect gonad maturation and the spawning process.